LEVEL OF COMMUNICATION AS A PSYCHOLOGICAL RESOURCE - NAUMENKO, N.; SHELESTOVA, O. (Herald of Kyiv Institute of Business and Technology, 2024)
In the modern world, where communication plays a pivotal role, the level of communication culture becomes a significant psychological resource. This article examines important aspects of communication culture, taking into account history, traditions, identity, and cultural codes. In today’s changing world, it is important to strike a balance between preserving traditions and being open to new ideas and cultural exchanges. The transformation of cultural identity can serve as a stimulus for the development and improvement of society by adapting to changes in the sociocultural environment. Moreover, education is a key factor in the development of cultural identity and society as a whole. The essence of a person consists of a close interweaving of material and spiritual. Civilization is defined as a way for humans to survive in a changing environment, encompassing the development of appropriate technologies to provide physical comfort and adaptation to adverse natural conditions. Instead, culture represents the opposite way of survival, which is based on the adaptation of a person to the world through the acquisition of psychological comfort and self-change. It modifies the perception of the world and the individual himself, ensuring internal stability. Unlike civilization, which generates material values, culture generates ideal, spiritual values, which can mean more to a person than material goods. In the 21st century there will be a partial transformation of existing identities and a juxtaposition of different identity models. This process will be complex and will involve the interaction of various cultural influences, the search for new ways of identification in the conditions of globalization and cultural diversity. Therefore, the transformation of cultural identity plays an important role in the development of modern society.